PENGARUH PROFESIONALISME APARAT BIROKRASI TERHADAP KUALITAS PELAYANAN PUBLIK SATUAN POLISI PAMONG PRAJA DAN KEBAKARAN KABUPATEN MINAHASA SELATAN - TAWAANG, TASYA AGUITA; LENGKONG, FLORENCE; LONDA, VERY (JURNAL ADMINISTRASI PUBLIK, 2020)
Improving the quality of public services needed by Civil Servants and Freelance Workers not only in terms of quantity, but also requires the ability of professionalism that is directly proportional to the demands of the community. Human resource development in the ranks of government (public organizations) needs to be directed at improving professional skills accompanied by a spirit of service to the public (community). Professionalism of bureaucracy and public services is becoming an increasingly strategic policy issue, because it is included as one of the factors that become criteria to achieve the smoothness of the goals of an organization or agency. This uses quantitative descriptive methods and data collection techniques using questionnaires given forty respondents. The results of the validity and reliability tests show each question is valid and reliable. The results of this study indicate that when the Civil Service Police Unit increases professionalism (height) will encourage improvement quality of public services. . Keywords : Professionalism, Public Service Quality